International relations of the Asia Pacific
International Relations of the Asia-Pacific is an intellectually stimulating journal that addresses major issues and developments taking place in the Asia-Pacific. The journal is a meeting place where various issues are debated from refreshingly diverging angles, backed up by rigorous scholarship. The journal is open to all methodological approaches and schools of thought, including non-western theories of international relations.